Elderly people admitted to an intensive care unit: the nurse facing pressure injury prevention (Research, Society and Development, 2022)
Objective: to highlight, through an integrative literature review, studies that address the presence of pressure injuries in elderly patients admitted to an intensive care unit and the role of nurses in preventing this event. Method: this is an integrative literature review with a time cut selected between the years 2017 to 2022; the databases used were LILACS, PUBMED and BDENF. Results: after applying the necessary criteria for a literature review, the study sample consisted of 8 articles, 37.5% of them were published in 2017 and 2018 each, while 25% published in 2020, the base of most used data was PUBMED with 6 articles; the studies addressed aspects such as care and treatments in the prevention of PI in eldery patients in the ICU, as well as nursing care with the use of scales. Conclusion: through this review, it was possible to analyze the main nursing care regarding the prevention of pressure injuries in elderly patients hospitalized in the ICU, highlighting the importance of the professional nurse in the management of care for critically ill patients.